Practical Sitecore 8 Configuration and Strategy A User Guide for Sitecore's Content and Marketing Capabilities - Wicklund, Phillip (Apress : Imprint: Apress, 2015)
Practical Sitecore 8 Configuration and Strategy: A User Guide for Sitecore's Content and Marketing Capabilities offers a comprehensive overview of Sitecore's web content management solutions, and provides step-by-step guidance for configuring Sitecore's personalization, testing, and marketing automation capabilities. The book highlights strategies and best practices-taking it beyond just the "how to" procedures that can be found elsewhere. Sitecore was recently recognized as one of the most reputable and reliable web content management solutions (WCMS) in the marketplace. Thousands of companies use Sitecore to help manage their web and mobile digital properties. But because Sitecore is a very large and complex platform, marketers and end users often have difficulty coming up to speed on the technology. Practical Sitecore 8 Configuration and Strategy provides the solution you need to get started using Sitecore today. Practical Sitecore 8 Configuration and Strategy: Brings you up to speed on Sitecore without requiring a training class Provides the information in a clear, logical outline that takes users from simple, foundational concepts to more advanced concepts at the end Rounds out existing sources of documentation with strategies and best practices from real-world experience.